Application of Multiple Intelligence in Aqidah Moral Subjects at SMA Negeri 1 Jakarta - Annisa Nur Fadhilah; Totong Heri (al-Afkar, Journal For Islamic Studies, 2024)
As we know, the application of the Multiple Intelligence theory in the world of education has been widely researched before, and the majority shows good results and the theory is very useful if it can be adopted in the school learning system. As quoted in an international journal with the title "The Effectiveness Of Multiple Intelligences Based Teaching Strategy In Enhancing The Multiple Intelligences And Science Process Skills Of Junior High School Students", the research states that several benefits from applying Multiple Intelligence are that it can be a significant predictor of development. students' multiple intelligences, from being only oriented towards academic abilities, to being oriented towards multiple intelligences and focusing on the potential of each student. Other research quoted from the international journal "The Implementation of a Multiple Intelligences Teaching Approach: Classroom engagement and physically disabled learners" also says the same thing, that a teaching approach that uses multiple intelligences also contributes to a significant increase in students' multiple intelligences, namely, greater student participation in class. Not only that, the journal with the title "The Concept of Multiple Intelligences Perspective of the Al-Qur'an/Hadith and its Implications for Islamic Religious Education Learning.